Upregulation of matrilin‐2 expression in murine hepatic stellate cells during liver injury has no effect on fibrosis formation and resolution. (26th June 2014) - Hintermann, Edith; Bayer, Monika; Pfeilschifter, Josef M.; Deák, Ferenc; Kiss, Ibolya; Paulsson, Mats; Christen, Urs
Abstract Background & Aims Matrilins are a family of four oligomeric adaptor proteins whose functions in extracellular matrix assembly during pathophysiological events still need to be explored in more detail. Matrilin‐2 is the largest family member and the only matrilin expressed in the naive liver. Several studies demonstrate that matrilin‐2 interacts with collagen I, fibronectin or laminin‐111‐nidogen‐1 complexes. All these matrix components get upregulated during hepatic scar tissue formation. Therefore, we tested whether matrilin‐2 has an influence on the formation and/or the resolution of fibrotic tissue in the mouse liver. Methods Fibrosis was induced by infection with an adenovirus encoding cytochrome P450 2D6 (autoimmune liver damage) or by exposure to the hepatotoxin carbon tetrachloride. Fibrosis severity and matrilin‐2 expression were assessed by immunohistochemistry. Hepatic stellate cells (HSCs) were isolated and analysed by immunocytochemistry and Transwell migration assays. Results Both autoimmune as well as chemically induced liver damage led to simultaneous upregulation of matrilin‐2 and collagen I expression. Discontinuation of carbon tetrachloride exposure resulted in concomitant dissolution of both proteins. Activated HSCs were the source of de novo matrilin‐2 expression. Comparing wild type and matrilin‐2‐deficient mice, no differences were detected in fibronectin and collagen I upregulation and resolution kinetics as well as amount or location of fibronectin and collagen I production and degradation. Conclusions Our findings suggest that the absence of matrilin‐2 has no effect on HSC activation and regression kinetics, synthetic activity, proliferative capacity, motility, or HSC apoptosis.